Prevalence of renal impairment and use of nephrotoxic agents among patients with bone metastases from solid tumors in the United States. (8th February 2015) - Arellano, Jorge; Hernandez, Rohini K.; Wade, Sally W.; Chen, Kristina; Pirolli, Melissa; Quach, David; Quigley, Jane; Liede, Alexander; Shahinian, Vahakn B.
<x xml:space="preserve">Abstract</x> In patients with bone metastases secondary to solid tumors, the 5‐year prevalence was 43% for renal impairment (RI) and 71% for chronic kidney disease among evaluable RI patients. Whenever possible, treatments that are potentially less damaging for the kidney should be considered for patients with or predisposed to RI.